Experimental investigation of phase relations in Al-Co-Y ternary system. (March 2017) - Jiang, Yurong; Li, Xian; Jiang, Yun; Huang, Shuaixiong; Shi, Xi; Mao, Cun; Zhang, Ligang; Liu, Libin; Zheng, Feng
Abstract: Phase relations in the Al-Co-Y ternary system at 1173 K have been established by means of scanning electron microscopy (SEM), electron probe microanalysis (EPMA) and X-ray diffraction (XRD) techniques. Isothermal section at 1173 K of this system was constructed, which consists of 27 three-phase regions and 50 two-phase regions (27wider+23line). The ternary compound τ5 -AlCo2 Y2 has been confirmed to exist and the crystal structure has been preliminarily analyzed with pattern indexing method as well. The intermetallic phase Co2 Y, Co3 Y, Co7 Y2, Co5 Y, Co17 Y2, Al2 Y, τ4 -AlCoY and τ5 -AlCo2 Y2 were expressed as the formula of Alx Co2−x Y, Alx Co3−x Y, Alx Co7−x Y2, Alx Co5−x Y, Alx Co17−x Y2, Al2−x Cox Y, Al1+x Co1−x Y and Al1−x Co2+x Y2, respectively. Graphical abstract: Highlights: Phase relations of the Al-Co-Y ternary system at 1173 K was established. A new ternary compound τ5 has been confirmed to exist. The intermetallic phase Co2 Y, Co3 Y, Co7 Y2, Co5 Y, Co17 Y2, Al2 Y, τ4 and τ5 were expressed as the formula of Alx Co2−x Y, Alx Co3−x Y, Alx Co7−x Y2, Alx Co5−x Y, Alx Co17−x Y2, Al2−x Cox Y, Al1+x Co1−x Y and Al1−x Co2+x Y, respectively.